INOVASI PENDAFTARAN ONLINE DI RUMAH SAKIT UMUM DAERAH K.R.M.T WONGSONEGORO KOTA SEMARANG - Bramantyo Suryo Nugroho; Dyah Hariani (Journal of Public Policy and Management Review, 2018)
Innovation is an important aspect of public service. The existence of people's needs continuously increases with the development of the era is one of the factors needed innovation in the public service. Innovation must follow the times, especially in the field of information technology. An innovation is expected to help solve the problems that exist in society. Online registration innovation in hospitals K.R.M.T Wongsonegoro based on the existence of queue problems that can not be handled with previous programs. This research uses descriptive method with qualitative approach The result of this research is making online registration innovation in RSUD K.M.R.T Wongsonegoro Semarang City there is a process of innovation that can be seen from seeing opportunities, finding ideas, reviewing ideas, and implementation. While there are supporting and inhibiting factors seen from the process of online registration innovation. Supporting factors of online registration innovation are (1) There is a desire to change oneself, from being unable and from being ignorant to know; (2) The existence of freedom of expression; (3) Availability of facilities and infrastructure. While the inhibiting factors of online registration innovation are (1) No rewards or incentives; (2) Administrative pressure and obstacles and (3) Risk Aversion Culture.